The Restating of Financial Statements by REITs. (July 2017) - Adams, John C.; Hayunga, Darren K.; Rasmussen, Stephanie J.
This article is the first to examine financial restatements by real estate investment trusts (REITs). We provide a descriptive breakdown of the underlying causes of REIT restatements as well as overall and subsample analyses of stock market reactions to restatements from 2000 to 2011. REIT restatements occur for a large variety of accounting issues with the most common being expense-related (e.g., leases, depreciation). We find that the average market reaction for REIT restatements is negative 0.63%, which is less negative than non-REIT restatements. Further investigation reveals that a significant portion of REIT restatements result in large positive or negative returns, the most extreme of which appear to be a result of both the restatement and other news released simultaneously. Cross-sectional analysis shows that the most important determinant of restatement cumulative abnormal returns (CARs) is whether the restatement is a result of Securities and Exchange Commission (SEC) comment letters or involves an investigation by regulators, which lowers the CAR by 5.64%. Overall, the findings suggest that REIT restatements occur for a variety of reasons, and REIT investors place high value on quality financial statements.